OP0139 Targeting IL-6 by Both Passive or Active Immunization Strategies Prevents Inflammation-Driven Skin Fibrosis. (10th June 2014) - Avouac, J.; Desallais, L.; Fréchet, M.; Elhai, M.; Zagury, J.F.; Allanore, Y.
Abstract : Background: Interleukin 6 (IL-6) is a pleiotropic cytokine involved in inflammatory and autoimmune processes. Preliminary data have suggested that IL-6 might contribute to systemic sclerosis (SSc). Objectives: Our aim was to compare the efficacy of both passive and active immunization against IL6 to reduce skin fibrosis in complementary mouse models of scleroderma. Methods: We first evaluated the monoclonal IL-6R antibody MR16-1 in the mouse model of bleomycin-induced dermal fibrosis, reflecting early and inflammatory stages of SSc. Six-week-old DBA/2 mice received in parallel subcutaneous injections bleomycin (0, 5 mg/ml) and intraperitoneal (ip.) injection of MR16-1 or control antibody at a dose of 2 mg at day 0 followed by one ip. injection of 1 mg at day 7 and 14. Then, we assessed the merit of MR-16 in the tight skin (Tsk-1) mice, an inflammation-independent mouse model of skin fibrosis. Tsk-1 mice received a first ip. injection of 2 mg of MR16-1 or control antibody at the age of 5 weeks followed by one ip. injection of 1 mg once a week for 5 weeks. Thereafter, because of the drawbacks of anti-cytokine monoclonal antibodies, we developed an innovative strategy using active immunization against a small peptide derived from murine IL-6, which was performed in the mouse model of bleomycin-induced dermal fibrosis. Results: Passive immunization with MR16-1 exerted antifibrotic effects in the mouse model of bleomycin-induced dermal fibrosis: dermal thickness, hydroxyproline content and myofibroblast counts were reduced by 25±4% ( P =0.02), 30±6% ( P =0.007) and 45±7% ( P =0.005) respectively, compared to mice receiving control antibody. MR16-1 demonstrated no efficacy in Tsk-1 mice. Mice immunized against the mIS200 peptide derived from murine IL-6 exhibited in the bleomycin mouse model similar antifibrotic effects as passive immunization. We observed a significant reduction of dermal thickness by 20±3% ( P =0.02), hydroxyproline content by 25±4% ( P =0.005) and myofibroblast counts by 41±9% ( P =0.01), compared to the group immunized against the carrier protein alone. Conclusions: We demonstrated that passive and active immunization targeting IL-6 had similar antifibrotic properties in a mouse model of inflammation-driven dermal fibrosis. Translation to human disease is now required, and targeting early and inflammatory stages of SSc sounds the most appropriate. This strategy is currently under investigation in a phase-3 clinical trial assessing the efficacy of tocilizumab to improve skin involvement in patients with early diffuse SSc. Our results also highlight the relevance of active immunotherapy that might be an avenue for IL6 axis in immunotherapy in a near future. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3478